The Effect of Shipbuilding Material Type on Biofouling Growth at Boom Marina, Banyuwangi, East Java, Indonesia - Wazirotus Sakinah; Ramli Firdaus Kusnadi; Dwi Bagus Prasetiaji; Pandu Prasetya Aji; R. Puranggo Ganjar Widityo; Franciscus Xaverius Kristianta (Department of Marine Sciences, Trunojoyo University of Madura, Indonesia, 2023)
ABSTRACTThe presence of biofouling has an impact on the ship’s performance, which is reduced to require more fuel, in the end, it contributes significantly to cost increases. Biofilms provide a suitable substrate for the growth of microorganisms. Ship hull as a substrate for biofilms has many kinds of material. Steel, wood, laminated bamboo, and fiber are often used for ship hulls. Different material makes different characteristics of substrate for biofilms. The aim of this research is to determine the growth rate of biofouling in each shipbuilding material and to find out which vessel material is suitable for use in the Bali Strait. The experiment was located in Boom Marina, Banyuwangi. The materials used in this research are wood, laminated bamboo, and fiber. The daily growth rate (DGR) is calculated every week of observation. Wood had the most biofouling with a DGR of 2,646 g/day. Laminated bamboo had the least biofouling in this research after 2 months of immersion with a DGR of 0,086 g/day. Keywords: Biofouling, shipbuilding material, daily growth rate.